Digital Financial Transformation And Artificial Intelligence In Improving Corporate Financial Performance - Yusran Daeng Matta; Amirudin (International Journal of Management and Business Economics, 2026)
The rapid development of digital technologies has transformed financial management practices and reshaped organizational performance in the digital economy. This study aims to examine the role of digital financial transformation, including artificial intelligence (AI), financial technology (fintech), big data analytics, and cloud-based financial systems, in improving corporate financial performance and supporting strategic decision-making. The study employs a qualitative descriptive approach through a literature review of academic journals, industry reports, and relevant publications on digital finance and financial innovation. The findings reveal that digital financial transformation contributes significantly to key financial performance indicators, including cost efficiency, profitability, financial reporting accuracy, risk management effectiveness, and decision-making quality. AI-driven analytics enable organizations to forecast financial trends, identify potential risks, and optimize resource allocation more effectively. Additionally, fintech and digital banking solutions enhance transaction speed, accessibility, and financial inclusion. Despite these benefits, organizations face challenges related to cybersecurity risks, regulatory compliance, implementation costs, and limited digital competencies among employees. This study contributes to the literature by highlighting the strategic importance of integrating digital finance and AI into financial management practices to achieve sustainable growth, financial resilience, and long-term competitive advantage in an increasingly digital business environment.